2023
DOI: 10.1186/s13018-023-03984-2
|View full text |Cite
|
Sign up to set email alerts
|

MiR-320a upregulation improves IL-1β-induced osteoarthritis via targeting the DAZAP1 and MAPK pathways

Abstract: Purpose Osteoarthritis (OA), a constant illness described by articular cartilage degeneration, usually manifested by joint pain and helpless development. Numerous literatures suggest that microRNAs play an important regulatory role in OA, yet the role of miR-320a in OA remains largely obscure. Materials and methods To evaluate the expression of miR-320a mRNA, quantitative real-time polymerase chain reaction was used. Cell counting kit-8 assay, Edu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Upregulated miR-223-3p inhibited apoptosis and the inflammatory response in chondrocytes induced by IL-1β by directly targeting NLRP3 [51]. By targeting the DAZAP1 and MAPK pathways, upregulated miR-320a improved IL-1β-induced osteoarthritis by enhancing chondrocyte proliferation, reducing apoptosis, and decreasing inflammatory response [52]. The miR-320a also played a role in protecting cartilage against degeneration by regulating the protein expression levels of BMI-1 and RUNX2 in chondrocytes [53].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated miR-223-3p inhibited apoptosis and the inflammatory response in chondrocytes induced by IL-1β by directly targeting NLRP3 [51]. By targeting the DAZAP1 and MAPK pathways, upregulated miR-320a improved IL-1β-induced osteoarthritis by enhancing chondrocyte proliferation, reducing apoptosis, and decreasing inflammatory response [52]. The miR-320a also played a role in protecting cartilage against degeneration by regulating the protein expression levels of BMI-1 and RUNX2 in chondrocytes [53].…”
Section: Discussionmentioning
confidence: 99%
“…In A-ASC-EVs, miR-320a was also upregulated and has been reported in the literature to be important in the regulation of OA, involving the ERK/JNK/MAPK pathway. Indeed, in vitro experiments demonstrated that overexpression of miR-320a restored chondrocyte proliferation inhibited by IL-1β, and reduced apoptosis and inflammatory response [ 43 ].…”
Section: Discussionmentioning
confidence: 99%